2013
DOI: 10.1038/ncomms3482
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between apparent viscosity and wettability in nanoconfined water

Abstract: Understanding and manipulating fluids at the nanoscale is a matter of growing scientific and technological interest. Here we show that the viscous shear forces in nanoconfined water can be orders of magnitudes larger than in bulk water if the confining surfaces are hydrophilic, whereas they greatly decrease when the surfaces are increasingly hydrophobic. This decrease of viscous forces is quantitatively explained with a simple model that includes the slip velocity at the water surface interface. The same effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
242
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 247 publications
(266 citation statements)
references
References 32 publications
20
242
0
Order By: Relevance
“…This is possible when the vibrating AFM tip dissipates most of its energy within the interfacial liquid, without significant interaction between the tip and the solid 30,31 . In this regime, hereafter referred to as 'interfacial dissipation microscopy' (IDM), information about the local interfacial energy is contained in the phase image, acquired simultaneously with the topography image of the interface and is related to the local dynamics of the liquid probed by the tip 40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…This is possible when the vibrating AFM tip dissipates most of its energy within the interfacial liquid, without significant interaction between the tip and the solid 30,31 . In this regime, hereafter referred to as 'interfacial dissipation microscopy' (IDM), information about the local interfacial energy is contained in the phase image, acquired simultaneously with the topography image of the interface and is related to the local dynamics of the liquid probed by the tip 40,41 .…”
Section: Resultsmentioning
confidence: 99%
“…Using the experimental bulk water viscosity η = 10 −3 Pa s, the corresponding slip lengths for graphene and BN are 10.4 ± 2.2 and 3.3 ± 0.6 nm, respectively. Overall water slippage on graphene and BN is characteristic of hydrophobic surfaces with a low friction coefficient, while on hydrophilic surfaces such as mica, silicon or graphene oxide slippage is significantly inhibited with sub-nm slip lengths [38,39]. To rationalize the difference in the two friction coefficients in terms of structural and energetic contributions, we compute the free energy profile of water within the contact layer ∆G(x, y), defined as ∆G(x, y) = −k B T ln P O (x, y).…”
mentioning
confidence: 99%
“…In small-amplitude AFM measurements of squeeze-out dynamics, conclusion regarding slip could not arrived at [9]. Ortiz-Young et al have fitted oscillatory shear data using an AFM to a model based finite slip [22]. The measurements on wetting (θ ≈ 0…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions regarding viscosity of nanoconfined water are difficult to reach owing to possible surface effects such as surface registry and finite slip at the boundary [6,22]. Although no-slip boundary condition is largely valid for bulk flows, it is suggested that there is a possibility of finite slippage when liquid flows through, or is squeezed out of the gap which is of the order of few nm [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation